Uji Hepatoprotektif Fraksi N-Heksana Kulit Batang Jamblang (Syzygium Cumini (L.) Skeels) Ditinjau Dari Kadar Ast, Alt, Dan Albumin - Amal, Surya; Hidayah, Himyatul; Gunarti , Neni Sri; Mangunsong , Dhavid Twua (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
The liver plays an important role in the metabolism and detoxification of harmful substances in the body. One of the drugs that can cause liver damage if used excessively is paracetamol. Liver damage due to paracetamol is characterized by an increase in the levels of AST (aspartate aminotransferase) and ALT (alanine aminotransferase) enzymes as well as a decrease in albumin levels in the blood. The bark of the jamblang tree (Syzygium cumini) contains flavonoid compounds, tannins, and triterpenoids that have antioxidant properties and may possess hepatoprotective effects. This study aims to evaluate the effect of the n-hexane fraction of jamblang bark on liver function parameters in male Wistar strain white rats induced with paracetamol, and to determine the most effective dose. This study involved 20 rats divided into five treatment groups: negative control (paracetamol 1000 mg/KgBB), positive control (silymarin 50 mg/KgBB), and three test groups that were given n-hexane fraction at graded doses (50, 100, and 200 mg/KgBB). The treatment was given for 21 days, while paracetamol was administered from day 15 to day 21. The results showed that the levels of AST and ALT were significantly affected by the n-hexane fraction of jamblang bark at a dose of 50 mg/KgBB with p < 0.0001 for AST and p = 0.0002 for ALT. Meanwhile, albumin levels were significantly affected at a dose of 200 mg/KgBB with p = 0.0411. From the results, it can be concluded that the n-hexane fraction of jamblang bark has the potential as a hepatoprotective agent, especially at a dose of 50 mg/KgBW.